THE DETERMINANTS OF STOCK RETURNS - Tullah, Dewi Sarifah; Feri Noviyanti; Apriyanti, Erma (Jurnal RAK (Riset Akuntansi Keuangan), 2022)
This study aims to determine the effect of ROA, CR, PBV and MVA through a quantitative approach. The research population is LQ-45 Index company. Purposive sampling was used as a sampling technique with the criteria of LQ-45 companies that published financial reports on the Indonesia Stock Exchange in 2001-2020, thus the sample that met the criteria consisted companies. The analysis technique uses multiple linear regression with panel data with the help of Eviews 11 software. The result of the study prove that the ROA, PBV and MVA varables have and effect on stock returns, while beta and ROA variables have no effect on stock returns. Investors companies that are their investment target, because these ratios have been proven to effect stock returns.